ENERGY CONVERSION FROM WOODY BIOMASS STUFF: POSSIBLE MANUFACTURE OF BRIQUETTED CHARCOAL FROM SAWMILL-GENERATED SAWDUST - Han Roliadi; Gustan Pari (Indonesian Journal of Forestry Research, 2006)
There are three dominant kinds of wood industries in Indonesia which consume huge amount of  wood materials as well as generate considerable amount of  woody waste stuffs, i.e. sawmills, plywood, and pulp/paper. For the two latest industries, their wastes to great extent have been reutilized in the remanufacturing process, or burnt under controlled condition to supplement their energy needs in the corresponding factories, thereby greatly alleviating environmental negative impacts.  However, wastes from sawmills (especially sawdust) still often pose a serious environmental threat, since they as of this occasion are merely dumped on sites, discarded to the stream, or merely burnt, hence inflicting dreadful stream as well as air pollutions. One way to remedy those inconveniences is by converting the sawdust into useful product, i.e. briquetted charcoal, as has been experimentally tried. The charcoal was at first prepared by carbonizing the sawdust wastes containing a mixture of the ones altogether from the sawing of seven particular Indonesia's wood species, and afterwards was shaped into the briquette employing various concentrations of starch binder at two levels (3.0 and 5.0 %) and also various hydraulic pressures (1.0, 2.5, and 5.0 kg/cm2).  Further, the effect of those variations was examined on the yield and qualities of the resulting briquetted charcoal.The results revealed that the most satisfactory yield and qualities of the briquetted sawdustcharcoal were acquired at 3 % starch binder concentration with 5.0 kg/cm2 hydraulic pressure. As such, the briquette qualities were as follows: density at 0.60 gram/cm3, tensile strength 15.27 kg/cm2, moisture content 2.58 %, volatile matter 23.35 %, ash content 4.10 %, fixed carbon 72.55 %, and calorific value 5,426 cal/gram. Those qualities revealed that the experimented briquetted sawdust charcoal could be conveniently used as biomass-derived fuel.